A Wearable Soft Robotic Exoskeleton for Hip Flexion Rehabilitation - Miller-Jackson, Tiana M.; Natividad, Rainier F.; Lim, Daniel Yuan Lee; Hernandez-Barraza, Luis; Ambrose, Jonathan W.; Yeow, Raye Chen-Hua (Frontiers in Robotics and AI, 2022)
Leg motion is essential to everyday tasks, yet many face a daily struggle due to leg motion impairment. Traditional robotic solutions for lower limb rehabilitation have arisen, but they may bare some limitations due to their cost. Soft robotics utilizes soft, pliable materials which may afford a less costly robotic solution. This work presents a soft-pneumatic-actuator-driven exoskeleton for hip flexion rehabilitation. An array of soft pneumatic rotary actuators is used for torque generation. An analytical model of the actuators is validated and used to determine actuator parameters for the target application of hip flexion. The performance of the assembly is assessed, and it is found capable of the target torque for hip flexion, 19.8Nm at 30°, requiring 86kPa to reach that torque output. The assembly exhibits a maximum torque of 31Nm under the conditions tested. The full exoskeleton assembly is then assessed with healthy human subjects as they perform a set of lower limb motions. For one motion, the Leg Raise, a muscle signal reduction of 43.5% is observed during device assistance, as compared to not wearing the device. This reduction in muscle effort indicates that the device is effective in providing hip flexion assistance and suggests that pneumatic-rotary-actuator-driven exoskeletons are a viable solution to realize more accessible options for those who suffer from lower limb immobility.